A SYSTEMATIC REVIEW OF FINANCIAL MANAGEMENT PRACTICES IN DEVELOPING COUNTRIES: TRENDS, CHALLENGES AND FUTURE DIRECTIONS - Teguh Prakoso; Rina Apriliani (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
Trends, Challenges, and Future Directions is a comprehensive and structured study that analyses, evaluates, and synthesises current information on financial management practices in developing countries. The research method used is literature. The results show that there is an increasing adoption of financial technology, the importance of financial inclusion, and the need for adaptive regulation. Significant challenges include infrastructure limitations, digital divide, and macroeconomic instability. The research also explores future directions, including the potential of blockchain, artificial intelligence in risk management, and the development of sustainable finance models. In conclusion, despite facing various obstacles, financial management practices in developing countries show dynamic development with significant opportunities for innovation. The implications of these findings are relevant for policymakers, industry practitioners, and researchers in optimising financial management strategies in emerging contexts.